Le Makhzen est-il soluble dans la mondialisation ? - Jean-Luc Piermay (EchoGéo)
Through the economic and industrial dynamics, this paper examines how the building of territories has taken place in Morocco from one half-century. Among the public policies, the economic question is the main field of State intervention under the reign of Mohammed VI. But from Independence (1956) the building of the national territory has taken advantage of an unchanging strategy of integration, still visible through the policies applied to the spaces neighbouring the borders. On the other side, infra national territories are little taken into account, even often seen with suspicion, except as local projections of the social and political networks coming from the State authorities.